2012
DOI: 10.3892/ol.2012.782
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan, leucovorin and 5-fluorouracil (modified FOLFIRI) as salvage chemotherapy for frail or elderly patients with advanced gastric cancer

Abstract: Abstract. We retrospectively evaluated the efficacy and safety of the modified FOLFIRI regimen in frail or elderly patients with advanced gastric cancer (AGC). We reviewed 24 frail [Eastern Cooperative Oncology Group performance status (ECOG PS) of 2] or elderly (65 years or over) patients with AGC who received the modified FOLFIRI regimen as salvage chemotherapy. Patients received irinotecan 150 mg/m 2 and leucovorin (LV) 100 mg/m 2 as a 2 h intravenous infusion, followed by 5-fluorouracil (5-FU) 2,000 mg/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Most patients in this study had an ECOG PS of 0–1 (83.4%) and were in a first‐line setting (92.9%). In another study reported by Kim and colleagues, 75% of patients were ECOG PS 2, and 45.8% were older than 65 years . The response rate was 12.5%, the median time to progression was 2 months, and the median OS was 5.4 months.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Most patients in this study had an ECOG PS of 0–1 (83.4%) and were in a first‐line setting (92.9%). In another study reported by Kim and colleagues, 75% of patients were ECOG PS 2, and 45.8% were older than 65 years . The response rate was 12.5%, the median time to progression was 2 months, and the median OS was 5.4 months.…”
Section: Discussionmentioning
confidence: 86%
“…In metastatic GC, previous studies suggest that irinotecan‐based doublet regimens could be an active treatment option in elderly patients . Fonck et al reported that patients with advanced or metastatic GC aged 70 years or older showed a response rate of 26%, a median PFS of 7 months, and a median OS of 10 months .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A baseline MRI showed 3 liver metastases, with largest lesion in the right lobe measuring 9.4 cm in the largest diameter. She was started on aflibercept and FOLFIRI (5-fluorouracil, leucovorin, and irinotecan) repeated every 2 weeks, with the first cycle on 06/17/2013, receiving intravenously aflibercept = 4 mg/Kg, irinotecan = 150 mg/m 2 , leucovorin = 100 mg/m 2 , and fluorouracil = 2000 mg/m 2 [ 16 ]. After the first cycle the patient underwent radioembolization with yttrium 90 resin microspheres targeting the largest right lobe hepatic tumor (07/03/13).…”
Section: Case Reportmentioning
confidence: 99%
“…Previous studies have indicated the superiority of systemic chemotherapy compared to best supportive care (BSC) in patients with advanced or recurrent GC (3)(4)(5) and several phase III trials investigating systemic chemotherapy in advanced GC patients have been conducted (6)(7)(8)(9)(10)(11). Recently, several clinical trials assessed the tolerability or efficacy of systemic chemotherapy, including adjuvant chemotherapy, in geriatric patients with advanced or recurrent GC and demonstrated its feasibility (12)(13)(14)(15)(16)(17). However, the effect of systemic chemotherapy in the prognosis of geriatric patients with advanced or recurrent GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%